When to Use Amisulpride in Adolescents: A Retrospective Chart Examination of Inpatients. Issue 3 (11th May 2022) - Tuncturk, Mustafa; Ermis, Cagatay; Saglam, Yesim; Can, Merve; Yuksel, Ayse Sena; Akca, Dilara; Alarslan, Sezen; Atay, Ayca; Ciray, Remzi Ogulcan; Turan, Serkan; Karacetin, Gul
Abstract: Purpose/Background: Despite increasing interest in amisulpride, current knowledge about its use in the pediatric population is scarce. This chart review aimed to investigate the use of amisulpride in a naturalistic adolescent population. Methods/Procedures: Electronic medical records of a tertiary care adolescent inpatient unit were screened between January 2015 and April 2021. Sociodemographic data and all clinical information were collected via data collection forms, and targeted symptoms were obtained from patients' files. Patients with early-onset psychotic disorders (n = 58), bipolar I disorder (n = 29), major depressive disorder (n = 14), and other psychiatric diagnoses (n = 9) were included. Treatment response was defined as a Clinical Global Impression–Improvement of at least much improvement after treatment. Findings/Results: Median titration rate of amisulpride was 400 mg/wk, and the maximum administered daily dose ranged between 100 and 1200 mg/d. The maximum daily dose and number of previous antipsychotics were higher in the early-onset psychotic disorder group. Persistent positive symptoms and resistance to previous treatments were leading causes for amisulpride treatment. Other indications were also impulsive/disruptive behaviors, antipsychotic adverse effects, depressive symptoms, somatic complaints, and abnormalities in liver function tests. Finally, patients with lower daily treatment doses and more previous antipsychotic trials are less likely to benefit from the treatment. Implications/Conclusions: Persistent psychotic/mood symptoms, impulsive/disruptive behaviors, and abnormalities in liver function tests were reasons for the amisulpride treatment in adolescents. Randomized placebo-controlled trials are needed to evaluate the efficacy and safety of the treatment in adolescents.